Eksplorasi Pembelajaran dengan Keterlibatan Langsung Pasien pada Pendidikan Profesi Dokter Gigi - Nur HN Prastiyani; Estivana Felaza; Ardi Findyartini (Majalah Sainstekes, 2020)
Background: Clinical stage learning in dentistry provides broad opportunities for students to give services directly to patients (chairside teaching). This certainly requires a great deal of attention to patient safety, so there is a need for supervision and giving feedback in learning. This study aimed to explore learning with the direct involvement of patients in clinical dental stage in dentistry. Methods: This was a qualitative study with a case study design, conducted from January to April 2019. Data collection was carried out through in-depth interviews and focus group discussions (FGD) with clinical supervisors and clincal students at the Dentistry, Universitas Yarsi. Data triangulation was carried out by observation of the implementation of chairside teaching. The data obtained were analyzed qualitatively. Results: In-depth interviews with 5 policy makers and FGDs with 2 groups of clinical supervisors (n = 8 and n = 6), and 2 groups of clincal students (n = 8 each) produced 3 themes. These three themes are the role of clinical teachers, the learning environment with patients, and the role of students. Conclusion: Supervision had been carried out in chairside teaching but it was not optimal yet. Therefore, it is necessary to adjust the level of supervision which is supported by providing constructive feedback to ensure patient safety and help students achieve the expected competencies.